Rethinking Justice: The Urgent Need to Simplify Legal Appeals and Cassation for Faster Administrative Court Decisions - Hakim, Putri Balqis Nuril; Rochman, Aulia; Alkadri, Riska; Maritah, Martitah (Indonesian State Law Review, 2024)
The efficiency of procedural examinations in Indonesia’s state administrative courts is essential for ensuring timely justice, especially in cases requiring urgent resolution. However, the current appeals and cassation processes often extend the overall timeline, undermining the court's ability to address urgent matters swiftly. While the initial procedural examination may be expedited, the subsequent appeal and cassation stages follow the same cumbersome steps as ordinary procedures, leading to significant delays—sometimes spanning several months. This prolonged timeline is particularly concerning when quick resolution is critical, as it can hinder the effective administration of justice. This study examines the necessity of simplifying the legal appeals and cassation processes to ensure faster and more efficient case resolutions in state administrative courts. Using a normative juridical research method, the paper assesses the inefficiencies of the current system, highlighting the urgent need for reform. It draws on Lawrence M. Friedman’s legal system theory to identify gaps within the existing framework that contribute to delays and proposes strategic interventions to streamline these processes. The findings suggest that, in addition to simplifying procedural measures, the integration of technology—such as an e-court system—could significantly expedite the appeal and cassation processes. By embracing digital solutions, administrative courts can reduce case backlogs and enhance efficiency, thus improving the overall responsiveness of the judicial system. This research contributes novel insights into how legal procedures can be reformed to better meet the demands of urgent cases. The study emphasizes the critical importance of judicial efficiency and technological innovation, offering actionable recommendations for policymakers to improve administrative justice in Indonesia.